Toward Conductive Polymer-Based Soft Milli-Robots for Vacuum Applications - Benouhiba, Amine; Rougeot, Patrick; Ouisse, Morvan; Clévy, Cédric; Andreff, Nicolas; Rabenorosoa, Kanty (Frontiers in Robotics and AI, 2019)
For the last two decades, the development of conducting polymers (CP) as artificial muscle by materials researchers and chemists has made it possible to establish a reliable and repeatable synthesis of such materials. CP-based milli-robots were essentially unknown in soft robotics, today presentations on them are increasing during robotics and smart materials forum. Indeed, this subclass of soft robots has reached an important moment in their history, exhibiting rather interesting features, based on established foundations in terms of modeling, control, sensing and planning in various applications. The purpose of this paper is to present the potential of conductive polymers-based soft milli-robots as high performance devices for vacuum applications. To that end, a tri-layered Polypyrrole-based actuator was first used inside a scanning electron microscope (SEM), characterized for different applied voltages and during a relatively long period time. Additionally, the tip positioning of the cantilever was also controlled using a closed-loop control. Furthermore, as a proof of concept for more complex soft milli-robot, an S-shaped soft milli-robot was model, using a hybrid model composed of two models a multi-physics model and a kenimatics model. It was then fabricated using laser machining, and finally characterized using its tip displacements. Polypyrrole-based soft milli-robots proved to have tremendous potential as high performance soft robots at microscale for wide range of applications, including SEM micro-manipulation as well as biomedical applications.